Random mutagenesis to enhance the toxicity of Bacillus thuringiensisCcry proteins against Earias vittella (F.) - Zaheer, Hafsa; Khurshid, Huma; Yunus, Fakhar-Un-Nisa; Manzoor, Farkhanda; Jabeen, Ghazala; Kanwal, Zakia (Penerbit Universiti Kebangsaan Malaysia, 2023)
Insecticidal proteins derived from Bacillus thuringiensis (Bt) are widely utilized in a variety of insect control applications, including sprays and transgenic crops. The development of resistance in pests, on the other hand, can lessen the effectiveness of Bt toxins. In this study, we made efforts to enhance the toxicity of two cry proteins Cry1Ac and Cry2Aa through random mutagenesis against cotton bollworm (Earias vitella), one of the most destructive cotton pests in Pakistan. Random mutagenesis is an important tool for elucidating protein structure-function relationships and for modifying proteins to enhance or change their characteristics. We focused on whole cry proteins for random mutagenesis through error-prone PCR and constructed a recombinant library of cry proteins. Sequence analysis of eight mutants showed the mutations of 34 different nucleotides in Cry1Ac and Cry2Aa genes. All mutants were spared for toxicity bioassays against 2nd instar larvae of spotted bollworm. Cry1Ac mutant RM1AcM4 (D242E) and Cry2Aa mutants RM2AaM2 (T354A, T492R, F511L, G585E, D606Y) showed enhanced toxicity as compared to proteins without mutation. These two mutants comprise the mutations in domain-II of cry proteins important in specificity determining regions on midgut receptors in insect pests.